Effect of noninvasive vagus nerve stimulation on acute migraine: An open-label pilot study. (October 2014) - Goadsby, PJ; Grosberg, BM; Mauskop, A; Cady, R; Simmons, KA
Background: We sought to assess a novel, noninvasive, portable vagal nerve stimulator (nVNS) for acute treatment of migraine. Methods: Participants with migraine with or without aura were eligible for an open-label, single-arm, multiple-attack study. Up to four migraine attacks were treated with two 90-second doses, at 15-minute intervals delivered to the right cervical branch of the vagus nerve within a six-week time period. Subjects were asked to self-treat at moderate or severe pain, or after 20 minutes of mild pain. Results: Of 30 enrolled patients (25 females, five males, median age 39), two treated no attacks, and one treated aura only, leaving a Full Analysis Set of 27 treating 80 attacks with pain. An adverse event was reported in 13 patients, notably: neck twitching ( n = 1), raspy voice ( n = 1) and redness at the device site ( n = 1). No unanticipated, serious or severe adverse events were reported. The pain-free rate at two hours was four of 19 (21%) for the first treated attack with a moderate or severe headache at baseline. For all moderate or severe attacks at baseline, the pain-free rate was 12/54 (22%). Conclusions: nVNS may be an effective and well-tolerated acute treatment for migraine in certain patients.